Contemporary Belarusian Dialects in Lithuania (Šalčininkai Region) - Jankowiak, Mirosław (Slavistica Vilnensis, 2020)
The aim of the article is to present contemporary Belarusian dialects in south-eastern Lithuania (in the Šalčininkai region), which have not been the subject of comprehensive linguistic research so far. The basis of the analysis is mainly the author’s own materials and materials taped by other dialectologists. The structure of these Belarusian dialects (selected features in phonetics, morphology, syntax, vocabulary and phraseology) as well as the sociolinguistic aspect of their use in a multilingual environment are demonstrated in the article. The analysis of the collected material shows that the structure of Belarusian dialects in the study area is well-preserved. Belarusian dialectologists regard the Belarusian dialect in the Vilnius Region as a south-western dialect, which should be described in detail. In the statements of interlocutors, one can note the phonetic, morphological and syntactic features typical of: the south-eastern dialect, the Central Belarusian dialect, the Grodno-Baranovichy group of the south-western dialects and the two so-called dialectal zones: western and north-western. On the one hand, it is a territory shaped by two dialectal massifs and one dialect group, on the other hand, it has been influenced by Baltic and Polish for hundreds of years. Particularly noteworthy is the lexis. Decades of coexistence of Belarusians, Lithuanians and Poles on this territory contributed to the fact that in Belarusian dialects there are numerous borrowings from Lithuanian and Polish (and their dialects).